2018
DOI: 10.4066/2591-7951.1000058
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Effects of Phytochemicals and Medicinal Herbs for Cancer Prevention and Treatment

Abstract: Cancer has a major impact on society across the world. It is one of the major causes of death, with approximately 1.7 million new cases expected to be diagnosed in the United States and 600,000 people will die from the disease. Worldwide statistics in 2012 reported over 14 million new cases and 8.2 million cancer-related deaths. New cases are expected to rise by about 70% over the next 20 years. The current standard of care, surgery, chemotherapy, and radiation has not proved to be highly effective and comes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…In fact, phytocompounds have been reported to enhance the anticancer activity of conventional drugs and show synergistic effects with conventional drugs . Due to the variety of reported biological and pharmacological properties including antimetabolic, immunomodulatory, anti-inflammatory, antioxidant, selective toxicity for cancer cells, oral route of administration, ease of availability, and their preferred acceptance by patients, plant-based compounds are considered a strong contender for therapeutic intervention . Although phytocompounds are shown to be generally safe and beneficial, toxic effects of these compounds are also reported.…”
Section: Phytocompounds Inhibiting Metabolism Of Cancermentioning
confidence: 99%
“…In fact, phytocompounds have been reported to enhance the anticancer activity of conventional drugs and show synergistic effects with conventional drugs . Due to the variety of reported biological and pharmacological properties including antimetabolic, immunomodulatory, anti-inflammatory, antioxidant, selective toxicity for cancer cells, oral route of administration, ease of availability, and their preferred acceptance by patients, plant-based compounds are considered a strong contender for therapeutic intervention . Although phytocompounds are shown to be generally safe and beneficial, toxic effects of these compounds are also reported.…”
Section: Phytocompounds Inhibiting Metabolism Of Cancermentioning
confidence: 99%
“…Recently, plant-based products have gained global interest from researchers looking to discover drugs of plant-based origins for use against cancer; a literature survey further summarised the anticancer activity of these phytochemical-rich plants, demonstrating their cytotoxic effect against different cancer cell lines [9][10][11][12][13][14][15][16][17]. Apart from the anticancer activity displayed by plants of medicinal importance, by modulating the signalling cascades correlated with cell cycle regulation and apoptosis, it has also been found that these plants display potent anti-inflammatory, antioxidant, and chemotherapeutic effects [12][13][14][15][16][17][18]. Interestingly these phytochemicals exhibit more cytotoxic effects on cancer cells than on normal cells [6,19] due to their pro-oxidant or antioxidant role depending on their exposure dose and vicinity [6].…”
Section: Introductionmentioning
confidence: 99%
“…have clinically proven to be bene icial in cancer therapy (Elvin-Lewis, 2001;Li, 2015). As per FDA (Food and Drug Administration) 60-75% phytochemicals and isolated active compounds are approved as valid chemo preventive agents (Jacobs, 2018). Phytochemicals currently practiced as anticancer chemo drugs include; taxol, vinblastine, vincristine, camptothecin derivatives, topotecan, etoposide and irinotecan.…”
Section: Introductionmentioning
confidence: 99%